Preservation of Donor Hearts Using Hypothermic Oxygenated Perfusion - Michel, Sebastian G. (Ann Transplant, 2014)
BACKGROUND: Hypothermic machine perfusion of donor hearts enables continuous aerobic metabolism and washout of toxic metabolic byproducts. We evaluated the effect of machine perfusion on cardiac myocyte integrity in hearts preserved for 4 h in a novel device that provides pulsatile oxygenated hypothermic perfusion (Paragonix Sherpa Perfusion(™) Cardiac Transport System). MATERIAL/METHODS: Pig hearts were harvested and stored in Celsior(®) solution for 4 h using either conventional cold storage on ice (4-h CS, n=6) or the Sherpa device (4-h pulsatile perfusion (PP), n=6). After cold preservation, hearts were evaluated using a non-working heart Langendorff system. Controls (n=3) were reperfused immediately after organ harvest. Biopsies were taken from the apex of the left ventricle before storage, after storage, and after reperfusion to measure ATP content and endothelin-1 in the tissue. Ultrastructural analysis using electron microscopy was performed. RESULTS: Four-hour CS, 4-h PP, and control group did not show any significant differences in systolic or diastolic function (+dP/dt, −dP/dt, EDP). Four-hour PP hearts showed significantly more weight gain than 4-h CS after preservation, which shows that machine perfusion led to myocardial edema. Four-hour CS led to higher endothelin-1 levels after preservation, suggesting more endothelial dysfunction compared to 4-h PP. Electron microscopy revealed endothelial cell rupture and damaged muscle fibers in the 4-h CS group after reperfusion, but the cell structures were preserved in the 4-h PP group. CONCLUSIONS: Hypothermic pulsatile perfusion of donor hearts leads to a better-preserved cell structure compared to the conventional cold storage method. This may lead to less risk of primary graft failure after orthotopic heart transplantation.